Comparative Molecular-Genetic Analysis of Francisella tularensis Strains Isolated in the Rostov Region in 2020 and Genome Sequences of the Strains Collected in Various Regions of the World - A. S. Vodop’yanov; R. V. Pisanov; S. O. Vodop’yanov; M. V. Tsimbalistova; N. L. Pichurina; V. M. Sorokin; N. V. Pavlovich; A. K. Noskov; А. С. Водопьянов; Р. В. Писанов; С. О. Водопьянов; М. В. Цимбалистова; et al. (Russian Research Anti-Plague Institute “Microbe”, 2023)
Six cultures of tularemia microbe from fallen and captured live animals were isolated during epizootiological monitoring in the steppe focus in the south-east of the Rostov Region in 2020 against the background of extensive epizootics in the populations of the common vole Microtus arvalis obscurus and the public vole Microtus socialis.The aim of the work was to develop an SNP-typing scheme and to conduct a comparative study of the phylogenetic relations between Francisella tularensis strains isolated in the Rostov Region (2020) and strains from other regions.Materials and methods. Genome-wide sequencing was performed on the MiSeq Illumina platform. The author’s software GeneExpert, PrimerM and VirtualPCR, written in the Java programming language, were used for the analysis.Results and discussion. The strains of tularemia agent, isolated on the territory of the Rostov Region in 2020, can be allocated to two different clusters. It is established that two strains of tularemia pathogen (F0884 and F0889) isolated in Turkey are genetically close to some isolates circulating in the Rostov Region. A unique INDEL marker characteristic of this group of strains has been identified. The comparison of our proposed typing scheme with the scheme of “canonical” SNPs has showed a fairly good consistency and convergence of results within large clusters, meanwhile using a set of 6626 SNPs allows for differentiating the strains within one canSNP type. It is revealed that the vaccine strain has a common canSNP type with clinical and natural strains. A set of SNP markers has been selected for comparative analysis. A new INDEL marker that enables intraspecific typing of F. tularensis has been discovered and the possibility of its application in vitro and in silico has been comfirmed. В 2020 г. при проведении эпизоотологического мониторинга в очаге степного типа на юго-востоке Ростовской области на фоне разлитой эпизоотии в популяциях обыкновенной полевки Microtus arvalis obscurus и общественной полевки Microtus socialis изолировано ...